ALGUNOS DATOS PARA EL ESTUDIO DE LOS PROCESOS DEGENERATIVOS DE LOS GRANULOCITOS NEUTROFILOS EN COLORACION POSTVITAM - GONZALEZ GUZMAN, IGNACIO (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1942)
In a control group of 7 dogs subjected to intense trauma of the inferior extremities, six died in a state of traumatic shock Of 6 dogs, similarly subjected to trauma but injected intra-cisternally with K phosphate soln, 4 dogs recovered completely The
BOL INST ESTUD MED BIOL
Keywords: DATOS, ESTUDIO, PROCESOS, DEGENERATIVOS, GRANULOCITOS, NEUTROFILOS, COLORACION, POSTVITAM; CIENCIAS MEDICAS; MEDICINA INTERNA; HEMATOLOGIA